Synthesis and study of branched hyaluronic acid with potential anticancer activity - Buffa, Radovan; Nešporová, Kristina; Basarabová, Ivana; Halamková, Pavlina; Svozil, Vít; Velebný, Vladimír (Carbohydrate polymers, 2019)
Conjugates of hyaluronic acid (HA) with biologically active molecules showed great potential in many applications. Oligomers of hyaluronic acid (oliHA) as possible regulators of biological processes and potential anti-cancer therapeutics, were reversibly attached via covalent bond on HA modified with an aldehyde group (HA-CHO) using bis-hydrazido or bis-oxyamino spacers. The structure of the final conjugates (HA-spacer-oliHA) was studied by advanced 2-dimensional NMR techniques in detail. The suggested synthetic strategy is simple, straightforward and can be used for the synthesis of various types of HA or oliHA conjugates. in vitro cytotoxicity assays showed selective activity of HA-spacer-oliHA conjugates against cancer cell lines in comparison with standard human fibroblasts.
Keywords: Hyaluronic Acid; Molecular Structure; Anti-cancer; Oligomers; Conjugate; molekulární struktura; lidé; Antineoplastic Agents; protinádorové látky; Hyaluronan; Cell Line, Tumor; Aldehyde; kyselina hyaluronová; fibroblasty; nádorové buněčné linie; Fibroblasts; Humans